Cervical Lymphadenopathy in Two Young Women The Same Rare Diagnosis with Different Presentations - Canadas, Sonia; Fernandes, Rita; Santos, Mónica; Vera-Cruz, Ana; Moreira, Ana Teresa (European Journal of Case Reports in Internal Medicine, 2020)
Kikuchi-Fujimoto disease (KFD) is a rare, benign and usually self-limiting disorder that more often affects young women, which is characterized by cervical lymphadenopathy and fever. Clinical presentation may be indistinguishable from other diseases, and its inclusion in the differential diagnosis of lymphoproliferative, infective and autoimmune diseases is essential. An association with systemic lupus erythematosus is acknowledged. We present 2 different cases of 2 young women with KFD; the first case highlights the classic diagnostic features of this rare entity, and the second, the findings when KFD occurs in association with systemic lupus erythematosus.